STRATEGI PENGOLAHAN SAMPAH DI D.I. YOGYAKARTA PASCA PENUTUPAN TPA PIYUNGAN: ANALISIS KONTEN PADA BERITA - Marya Yenita Sitohang; Yulinda Nurul Aini; Riza Fatma Arifa (Pangripta Sembada : Jurnal Perencanaan Pembangunan, 2026)
Piyungan final disposal site (TPA) has been permanently closed in May 2024, disrupting waste management in the Special Region of Yogyakarta. This paper aims to describe sentiments towards the closure of the Piyungan TPA, alternative strategies for waste management after the closure of the TPA, and the actors involved in it. Using a descriptive qualitative approach, this study analyzed the content of 88 news discussed waste management in Yogyakarta province after the closure of the TPA. Most of the news did not have sentiments towards the closure of the Piyungan TPA, but when they did, the sentiments were negative due to the accumulation of waste in several areas and the increasing frequency of waste burning among the community. However, some news provided positive sentiments and supported the closure of the Piyungan TPA considering the limited capacity and could be a momentum for changing the culture of waste management. Several waste management strategies have been carried out before and after the closure of the Piyungan TPA, both upstream, at the source of waste (generally involving a large role for the community in sorting waste), and downstream, which generally revolves around strengthening waste management facilities by the government. However, this study identified the lack of readiness of the government and the community in reforming waste management after the closure of the Piyungan TPA, as seen from the many downstream waste processing facilities that cannot be used, and the absence of significant changes in the culture of waste sorting among the community.